Fatigue crack growth behaviour of wire and arc additively manufactured ER70S-6 low carbon steel components - Ermakova, Anna; Mehmanparast, Ali; Ganguly, Supriyo; Razavi, Javad; Berto, Filippo (Springer, 2021)
The new emerging Wire and Arc Additive Manufacturing (WAAM) technology has significant potential to improve material design and efficiency for structural components as well as reducing manufacturing costs. Due to repeated and periodic melting, solidification and reheating of the layers, the WAAM deposition technique results in some elastic, plastic and viscous deformations that can affect material degradation and crack propagation behaviour in additively manufactured components. Therefore, it is crucial to characterise the cracking behaviour in WAAM built components for structural design and integrity assessment purposes. In this work, fatigue crack growth tests have been conducted on compact tension specimens extracted from ER70S-6 steel WAAM built components. The crack propagation behaviour of the specimens extracted with different orientations (i.e. horizontal and vertical with respect to the deposition direction) has been characterised under two different cyclic load levels. The obtained fatigue crack growth rate data have been correlated with the linear elastic fracture mechanics parameter ΔK and the results are compared with the literature data available for corresponding wrought structural steels and the recommended fatigue crack growth trends in the BS7910 standard. The obtained results have been found to fall below the recommended trends in the BS7910 standard and above the data points obtained from S355 wrought material. The obtained fatigue growth trends and Paris law constants from this study contribute to the overall understanding of the design requirements for the new optimised functionally graded structures fabricated using the WAAM technique.
Keywords: Additive manufacturing; WAAM; Structural integrity; Fatigue Crack growth